High Worry Severity is Associated with Poorer Acute and Maintenance Efficacy of Antidepressants in Late-Life Depression - Andreescu, Carmen (2009)
BACKGROUND: Comorbid anxiety symptoms are common in late-life depression (LLD) and predict poorer treatment outcomes. No research has delineated the impact of different dimensions of anxiety (such as worry/anxious apprehension and panic/anxious arousal) on treatment response in LLD. We explored the impact of the dimensions of worry and panic on acute and maintenance treatment outcomes in LLD. METHODS: We measured anxiety symptoms in 170 LLD subjects receiving protocolized treatment. Exploratory principal components analysis was used to delineate dimensions of anxiety symptoms. We defined sub-groups based on factor scores. We used survival analysis to test the association of pre-treatment anxiety dimensions with time to response and time to recurrence of LLD. RESULTS: The principal component analysis found two factors: “worry” and “panic”. Three sub-groups were defined: low panic-low worry, low panic-high worry, and high panic-high worry. The low panic-high worry and high panic-high worry sub-groups had longer time to response than the low panic-low worry sub-group. Time to recurrence was longer in low panic-low worry subjects randomized to drug. Among subjects with high worry, there was no difference between those with low versus high panic regarding both time to response and time to recurrence of LLD. CONCLUSION: High levels of worry were associated with longer time to response and earlier recurrence with pharmacotherapy for LLD. There was no additional effect of panic symptoms on treatment outcomes when accounting for the effects of excessive worry. These results suggest that worry symptoms should be a focus of strategies to improve acute and maintenance treatment response in LLD.